Labor and value creation processes in the sector of natural food production in Turkey - Küçük, Bermal. (Thesis (M.A.) - Bogazici University. Institute for Graduate Studies in the Social Sciences, 2016., 2016)
Demand for healthy and natural food has been increasing significantly, particularly among some segments of the middle and upper classes in metropolitan areas over the last decade in Turkey. This trend also has repercussions in the world of agriculture. We observe that an increasing number of farms have been established to meet this demand through organizing and coordinating agricultural production, especially in the southwestern cities of Turkey. This study examines the labor and value creation processes in the natural food production sector in Turkey. To that end, I scrutinize İpek Hanım Çiftliği, a farm located in the Nazilli district of Aydın, as a case study. The main argument is that value creation and capital accumulation are realized through the appropriation of women’s domestic labor and knowledge. Women’s labor and knowledge appear as a natural resource available for use as capital in this sector. This study also argues that the romanticization of past history and of nature are two other important strategies for capital accumulation in this sector. This study is based on field research and interviews conducted with the women working on the farm and the owner of the farm. It is also based on discourse analysis. I analyze the texts which have been created for the promotion of food products and which are sent to customers via e-mail, and I highlight the important themes of the discourse employed in them.
Keywords: Natural foods industry -- Turkey.; Value analysis (Cost control); Agricultural development projects -- Turkey.